Analisis Model SITR dengan Tes Viral Load Pada Penyebaran Penyakit HIV di Indonesia - Kristanti, Anggita Retno; Vita Kusumasari (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells in the body. Until now, HIV is still one of the world's health problems. Mathematical models have an important role in understanding the dynamics of a disease epidemic. The purpose of this study is to model and analyze the spread of HIV disease in Indonesia using the SITR model with viral load tests. This model divides the population into four subpopulations, namely Susceptible (S) or subpopulations that are susceptible to contracting the disease, Infected (I) or subpopulations that are infected with HIV, Treatment (T) or subpopulations that are infected with HIV and receive ARV treatment, and Recovery (R) or subpopulations whose viral load test results are suppressed after taking ARV treatment. The model analysis was conducted with model assumptions, parameter estimation, equilibrium point determination, equilibrium point stability analysis, and numerical simulation using Maple18. Based on the analysis, the value of =10,52749285 is obtained, which means that the model is asymptotically stable towards the endemic equilibrium point.